Non-pharmacological measures for pain relief at term newborns: integrative review (Research, Society and Development, 2020)
Objective: To describe the non-pharmacological strategies used for pain relief in newborns during painful procedures. Method: This is an integrative review. The data collection period occurred from 09/01/19 to 11/1/19 in the following databases: Health Sciences (LILACS), Cochrane Library (COCHRANE), Cumulative Index to Nursing and Allied Health Literature (CINAHL), and SciVerse Scopus (SCOPUS). Results: Eleven articles were selected, out of the total number of articles analyzed, (54.5%) of the references addressed non-harmacological measures such as high or moderate quality intervention to relieve procedural pain. The non-pharmacological measures for pain relief in newborns, the main measures found were: breastfeeding, non-nutritive sucking, sweet solutions such as glucose 25% or sucrose 24%, skin-to-skin contact, massage and rolling. Conclusion: Scientific production in Brasi needs to advance, mainly in the theme that involves low-risk newborns and pain management. The establishment of a care protocol proposal makes it possible to standardize newborn pain relief strategies, using non-pharmacological methods.